Influência do crescimento anormal de grão nas propriedades mecânicas de ligas superelásticas CuAlMnTiB e CuAlMn - Alcântara, Carlos Cássio de (2017)
In this work the inﬂuence of the various grain sizes, obtained by reﬁnement and treatment of abnormal grain growth, on the mechanical properties of the superelastic polycrystalline alloys CuAlMnTiB and CuAlMn were investigated. The alloys were prepared in an oven under an ambient atmosphere, thermally treated to obtain coarse grains and then characterized by optical microscopy, x-ray diffraction, traction and microhardness tests. It was noticed that activation of the abnormal grain growth is related to the presence of precipitates and the rate of heating. The alloy with reﬁners showed to be more sensitive to the activation of the process. In the XRD analysis it was possible to determine the austenitic phase β3, structure L21, the γ phase and the martensitic phase γ’. Through the tensile-test it was possible to note the inversely propotional relationship between the stress-induced martensitic (σy), the tensile strength limit (St) and the maximum strain (εmax) with the increase of the relative grain size (d/t). The microhardness test determined the hardness of the austenitic and martensitic phases.